Students’ wellbeing in positive higher education: conceptual frameworks and influencing factors - Li, Honghuan (Frontiers in Education, 2025)
Students’ wellbeing in higher education is increasingly recognized as a crucial factor for academic success and personal development. This narrative review examines how positive psychology frameworks contribute to college student wellbeing. Key findings indicate that student wellbeing is a multidimensional construct shaped by personal attributes, academic factors, and institutional context. Positive psychology provides a conceptual lens, including theories such as PERMA and self-determination, to understand and enhance wellbeing in university settings. The review highlights the need for holistic, proactive approaches that integrate wellbeing into the fabric of higher education. Implications include incorporating wellbeing skills into curricula, fostering supportive learning environments, and campus-wide policies that prioritize students’ mental health. By aligning educational practices with positive psychology, institutions can cultivate flourishing students poised to thrive academically and personally.